Bioremediation of Soil Contaminated with Diesel using Biopile system - Jabbar, Noor Mohsen; Kadhim, Estabriq Hasan; Mohammed, Alaa Kareem (Al-Khwarizmi Engineering Journal, 2018)
This study was focused on biotreatment of soil which polluted by petroleum compounds (Diesel) which caused serious environmental problems. One of the most effective and promising ways to treat diesel-contaminated soil is bioremediation. It is a choice that offers the potential to destroy harmful pollutants using biological activity. The capability of mixed bacterial culture was examined to remediate the diesel-contaminated soil in bio piling system. For fast ex-situ treatment of diesel-contaminated soils, the bio pile system was selected. Two pilot scale bio piles (25 kg soil each) were constructed containing soils contaminated with approximately 2140 mg/kg total petroleum hydrocarbons (TPHs). The amended soil: (contaminated soil with the addition of nutrients and bacterial inoculum), where the soil was mixed with 1.5% of sawdust, then supplied with the necessary nutrients and watered daily to provide conditions promoting microorganism growth. Unamended soil was prepared as a control (contaminated soil without addition). Both systems were equipped with oxygen to provide aerobic conditions, incubated at atmospheric temperature and weekly sampling within 35 days. Overall 75% of the total petroleum hydrocarbons were removed from the amended soil and 38 % of the control soil at the end of study period. The study concluded that ex-situ experiment (Bio pile) is a preferable, economical, and environmentally friendly procedure, thus representing a good option for the treatment of soil contaminated with diesel.